Squeezing flow of second grade liquid subject to non-Fourier heat flux and heat generation/absorption - Hayat, T.; Waleed Ahmed Khan, M.; Alsaedi, A.; Ijaz Khan, M. (Colloid and polymer science, 2017)
Two-dimensional squeezing flow of second grade fluid between two parallel plates is addressed. The lower plate is stretched while the upper plate is either moving away or towards the lower one. Temperature-dependent thermal conductivity is considered. Further, heat source/sink is present. Unlike the classical situation, the heat flux by Cattaneo-Christov theory is adopted instead of Fourier’s heat conduction law. Homotopic convergent solutions of velocity and temperature are developed and analyzed. Reduction in the thermal layer thickness is observed for Cattaneo-Christov heat flux model when compared with that of Fourier’s law of heat conduction. It is observed that velocity profile is enhanced by increasing the squeezing parameter. Also, a positive squeezing parameter enhances the thermal field due to a higher squeezing force applied on the fluid.